Turbulent entrainment in jets and plumes - Van,Reeuwijk M; Salizzoni,P; Craske,J (2015)
We perform direct simulation of a statistically steady jets, forced plume and pure plume in a neutral environment and present the value of the entrainment coefficient decomposed into 1) turbulence production; 2) buoyancy effects; and 3) deviations from self-similarity. The value of the decomposed entrainment coefficient is in excellent agreement with a direct estimate from the volume conservation equation. It is shown that the Priestley and Ball entrainment model describes the entrainment physics reasonably well.